Rekayasa Perangkat Lunak Aplikasi E-Report Layanan Pengaduan Masyarakat - Devi, Arfira Trisna; Fiansyah, Arif; Sari, Arinda Chintya; Maulana, Nanda Risky; Yulianti, Yulianti; Desyani, Teti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Information becomes very important in the process of developing a region or region without information it will be difficult for a region to develop, many aspects that can help the development process of a region, for example the construction of public facilities, building a good, comfortable and safe social environment etc. Without access to adequate information, aspects of the development of an area will be hampered and left behind, another negative impact is material losses and even worse casualties, because there is no information that develops from the area a-report in public services that was created as an information tool in responding to events quickly and effectively within the community. Which was conceptualized with a smart city design, to increase city efficiency in providing accurate and fast information services to the community. This application was designed with the water method plunge, where this method applies a sequential and systematic approach to the software development process, while for testing in this application, we use the black box method. Which later, the results of our design will produce applications that can increase the efficiency of the community in providing information that is integrated directly with government.